Analysis of Human Adaptability, Social Capital, and Business Innovation in Business Sustainability - Dwi Anjarini, Ary; Aria Mulyapradana; Aghus Jamaludin Kharis (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the role of Human Adaptability, Social Capital, and Business Innovation in supporting Business Sustainability among MSME actors. The research employed a Mixed Method approach with data collection techniques including observation, in-depth interviews, and questionnaires distributed to 83 MSME respondents in Pekalongan City and Regency. Quantitative analysis was conducted using Structural Equation Modeling–Partial Least Square (SEM-PLS), while qualitative data were utilized to strengthen the findings. The results indicate that Human Adaptability has a significant positive effect on Business Innovation, meaning that the higher the MSMEs’ ability to adapt to technology and market changes, the greater their opportunities to create innovation, which in turn significantly influences business sustainability. Social Capital also shows a significant positive impact on Business Innovation, emphasizing the importance of social networks and collaboration in fostering new ideas. Furthermore, Business Innovation strongly contributes to Business Sustainability, covering financial, social, and environmental aspects. However, the direct relationship between Human Adaptability and Business Sustainability is weaker compared to its mediated effect through innovation. These findings highlight that MSME sustainability is not only determined by adaptability and social networks but primarily by the ability to transform adaptability and social capital into concrete innovations. Therefore, strategies to enhance MSME competitiveness should focus on improving digital literacy, strengthening business networks, and providing innovation mentoring in products and business models to ensure survival in an increasingly dynamic business environment